Interpreting content, context and manufacture from use-residues in ceramic vessels from Southern Argentinean Puna - Babot, Maria del Pilar (2010)
Use-residue analysis from archaeological ceramic vessels is frequently directed to identify contents and to discuss functionality. Recently, Zucol and Mazzanti (2005) paid attention to different contamination sources for "use-residues", including ceramic and sedimentary matrix, and they proposed control sampling procedures. We agree with them and also, propose that residue analysis allows us to obtain specific information related to use, manufacture and context for archaeological artefacts. From an ample taphonomic point of view, this information can be understood not only in ?contamination? terms, but also as genuine data regarding natural and cultural processes of formation and transformation of archaeological record. In this paper, we analyze use-residues from six containers recovered as complete or in situ> broken vessels, in four partially contemporary archaeological contexts within Punta de la Peña 9 site, at Antofagasta de la Sierra, Catamarca (Southern Argentinean Puna). The vessels belongs to the second part of the first millennium AD and comes from two burials -Structure 2, PP9.II (López Campeny 2001) and Structure 1, PP9.I (González Baroni et al. 2007)-, a multiple activity place -Structure 3, PP9.I (Babot et al. 2006)- and a ritual deposit -PP9.I (Babot et al. 2007)-.Our research design starts with a review of archaeological assemblages that are spatially related to vessels (plant macro-remains, hearts, etc.) and of integrity and dynamic of their contexts of provenience. On this base, we propose hypothesis about the presence of microfossils in use-residue samples, belonging to ceramic and sedimentary matrix as well as cultural and natural processes, both contemporaneous and postdepositational to the discard of vessels. Besides, we follow Babot (2003, 2007) to establish cultural practices of plant processing -as an additional taphonomic factor- by analyzing starch grain damage and the whole microfossil assemblage. Finally, we carry out a dry and stratified sampling procedure for vessels (Babot 2004) to preserve provenance data for residues (base, body, neck, fresh fracture, macroscopic use residues, stains of probable postepositational origin, etc.). Results obtained allow us to identify aspects of use, manufacture and context for ceramic vessels from use-residue samples, on depending on their integrity and postdepositational history. Additionally, indicators of several cultural practices are recovered, that are directly or indirectly related to the use of vessels, such as processing procedures, burning of roofs and ritual disturb of deposits. As a corollary, we estate that it is possible to consider macrofossils labelled as ?contamination?, in a positive way, as information that goes far from the use of artefacts, to allow us to understand and cross-checking cultural and natural processes of formation and transformation of archaeological record.